2021
DOI: 10.1017/s0025315420001307
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth and mortality of the striped seabream Lithognathus mormyrus (Linnaeus, 1758) in the Gulf of Tunis (Central Mediterranean Sea)

Abstract: Despite the high commercial value of the striped seabream Lithognathus mormyrus (Linnaeus, 1758) in the Gulf of Tunis, biological data on its age, growth and exploitation rate are lacking. With the aim of estimating growth parameters, 516 individuals, ranging from 6–27.5 cm total length and from 3.5–293.5 g total weight, were collected from the artisanal fishing fleet between February 2014 and July 2016. The somatic growth presented a positive allometry and was described by the equation TW = 6.54 10−3TL3.213. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The catch of this species was 20 kg with an average length and weight of 20 cm and 107 g, respectively. [53] reported that the asymptotic length of this species is 30.18 cm in the Gulf of Tunis. L. mormyrus is found at depths ranging from 0 to 150 m, with a preference for water between 10 and 30 m [54].…”
Section: Resultsmentioning
confidence: 96%
“…The catch of this species was 20 kg with an average length and weight of 20 cm and 107 g, respectively. [53] reported that the asymptotic length of this species is 30.18 cm in the Gulf of Tunis. L. mormyrus is found at depths ranging from 0 to 150 m, with a preference for water between 10 and 30 m [54].…”
Section: Resultsmentioning
confidence: 96%